Heterogeneity on long-term disability trajectories in patients with secondary progressive MS: a latent class analysis from Big MS Data network - Signori, Alessio; Lorscheider, Johannes; Vukusic, Sandra; Trojano, Maria; Iaffaldano, Pietro; Hillert, Jan; Hyde, Robert; Pellegrini, Fabio; Magyari, Melinda; Koch-Henriksen, Nils; Sørensen, Per Soelberg; Spelman, Tim; et al. (Journal of neurology, neurosurgery, and psychiatry, 2023)
BACKGROUND: Over the decades, several natural history studies on patients with primary (PPMS) or secondary progressive multiple sclerosis (SPMS) were reported from international registries. In PPMS, a consistent heterogeneity on long-term disability trajectories was demonstrated. The aim of this study was to identify subgroups of patients with SPMS with similar longitudinal trajectories of disability over time. METHODS: All patients with MS collected within Big MS registries who received an SPMS diagnosis from physicians (cohort 1) or satisfied the Lorscheider criteria (cohort 2) were considered. Longitudinal Expanded Disability Status Scale (EDSS) scores were modelled by a latent class growth analysis (LCGA), using a non-linear function of time from the first EDSS visit in the range 3-4. RESULTS: A total of 3613 patients with SPMS were included in the cohort 1. LCGA detected three different subgroups of patients with a mild (n=1297; 35.9%), a moderate (n=1936; 53.6%) and a severe (n=380; 10.5%) disability trajectory. Median time to EDSS 6 was 12.1, 5.0 and 1.7 years, for the three groups, respectively; the probability to reach EDSS 6 at 8 years was 14.4%, 78.4% and 98.3%, respectively. Similar results were found among 7613 patients satisfying the Lorscheider criteria. CONCLUSIONS: Contrary to previous interpretations, patients with SPMS progress at greatly different rates. Our identification of distinct trajectories can guide better patient selection in future phase 3 SPMS clinical trials. Additionally, distinct trajectories could reflect heterogeneous pathological mechanisms of progression.
Keywords: chronicko-progresivní roztroušená skleróza; Multiple Sclerosis, Chronic Progressive; Persons with Disabilities; STATISTICS; MULTIPLE SCLEROSIS; registrace; Registries; lidé; Disease Progression; progrese nemoci; analýza latentních tříd; roztroušená skleróza; Latent Class Analysis; postižení; Humans; Multiple Sclerosis